Banking: conservative fundamentals and challenges of creativity - Strelnikov, Vladimir V. (Opción, 2020)
The study aims to investigate banking as conservative fundamentals and challenges of creativity via comparative qualitative research methods. As a result, the analysis of the dynamics of some banking indicators — capital, total assets, total profit — shows an increase in the banking resource potential. However, this growing potential, as an important factor in the market economy as a whole, is used less and less efficiently upon the same market criteria. In conclusion, banking at the present stage of development should be considered as one of the backbones in the process of the formation of the creative economy.